MANGANESE(II) DETERMINATION BY DIFFUSE REFLECTANCE SPECTROSCOPY - Ya. I. Simakina; I. I. Kuzmin; Yu. I. Fabelinsky; T. Kh. Chyong (Тонкие химические технологии, 2017)
Results of testing a prototype light-emitting diod miniphotometer for rapid and sensitive elements determination both in laboratory and in field conditions are presented. The new photometer consists of two devices providing measurements of absorbance and diffuse reflectance, having a joint system of data management, registration and presentation of the results. The measurements of absorbance were registered in the visible spectrum. The explored reaction of Mn(II) with 1-(2-pyridylazo)-2-naphthol and the new reaction with 2-(2-quinolinazo)-5-diethylaminophenol were used to verify the device’s metrological parameters. Spectra obtained by means of the proposed photometer were compared to those for commercial photometers. A computer algorithm considering the difference in light-emitting intensity between diods was developed. The possibility of determination down to 1 mkg/ml metal ions in liquid samples was shown.